Risk management in mergers and acquisitions: A case study Tata Corus merger - Agarwal, Riya (2009)
Mergers and acquisitions can be understood by managers to force turbulence in the environment. Despite the material failures rates of mergers and acquisitions, those pulling the trigger can make them work if they spend great care and development of their M&A deals. My research answers whether it is beneficial for the firm to incur risk management cost. The results reveals that on average, the company should adopt risk management strategies to maximise the gains in respect of risk the companies faces during mergers. The research considers casestudy of Tata and Corus merger. It determines the risk the company will face and the risk management strategy that the company should employ during and post mergers and acquisition. The research carries an ratio analysis to list the risk in the companies by considering ratios like return on equity, net profit ratio, debt equity ratio and Current ratio for a period of five years 2004-2009. The research also carries an experience survey to gain further insight in the Tata Corus deal.